Vegetarianism and breast, colorectal and prostate cancer risk: an overview and meta‐analysis of cohort studies. Issue 3 (6th October 2016) - Godos, J.; Bella, F.; Sciacca, S.; Galvano, F.; Grosso, G.
Abstract: Background: Vegetarian diets may be associated with certain benefits toward human health, although current evidence is scarce and contrasting. In the present study, a systematic review and meta‐analysis of prospective cohort studies was performed with respect to the association between vegetarian diets and breast, colorectal and prostate cancer risk. Methods: Studies were systematically searched in Pubmed and EMBASE electronic databases. Eligible studies had a prospective design and compared vegetarian, semi‐ and pesco‐vegetarian diets with a non‐vegetarian diet. Random‐effects models were applied to calculate relative risks (RRs) of cancer between diets. Statistical heterogeneity and publication bias were explored. Results: A total of nine studies were included in the meta‐analysis. Studies were conducted on six cohorts accounting for 686 629 individuals, and 3441, 4062 and 1935 cases of breast, colorectal and prostate cancer, respectively. None of the analyses showed a significant association of vegetarian diet and a lower risk of either breast, colorectal, and prostate cancer compared to a non‐vegetarian diet. By contrast, a lower risk of colorectal cancer was associated with a semi‐vegetarian diet (RR = 0.86, 95% confidence interval = 0.79–0.94; I 2 = 0%, P heterogeneity = 0.82) and a pesco‐vegetarian diet (RR = 0.67, 95% confidence interval = 0.53, 0.83; I 2 = 0%, P heterogeneity = 0.46) compared to a non‐vegetarian diet. The subgroup analysis by cancer localisation showed no differences in summary risk estimates between colon and rectal cancer. Conclusions: A summary of the existing evidence from cohort studies on vegetarian diets showed that complete exclusion of any source of protein from the diet is not associated with further benefits for human health.